Heat stress incidence and matchplay characteristics in women's grand slam tennis - Smith, M. T.; Reid, M.; Kovalchik, S.; Wood, T.; Duffield, R. (Journal of Science and Medicine in Sport, 2018)
Objectives: To explore the relationship of wet bulb globe temperature (WBGT) on heat-related incidents and alterations in matchplay and behavioural characteristics in women`s tennis at the Australian Open. Design: From 360 main draw Australian Open women's matches (2014-2016), data describing on-court calls for trainers, doctors, cooling devices and water, post match medical consults and matchplay characteristics were collated. Methods: Data were referenced against estimated WBGT and categorised into standard zones (zone 5: >32.3 °C, zone 4: 30.1-32.2 °C, zone 3: 27.9-30 °C, zone 2: 22.3-27.9 °C, zone 1: <22.2 °C). Generalized linear models assessed the association of WBGT zone on heat-related medical incidences, court call-outs and match characteristics. Results: With an increased estimated WBGT zone, there was an increase in total trainer calls (+19.5%/zone; p = 0.019), total doctor calls (+54.1%; p < 0.001), total calls for heat related incidents (+55.9%; p < 0.001), and cooling devices (+31.4%; p < 0.001) calculated from the regression slope. When match characteristics were adjusted for match quality, significant decreases (p < 0.001) in the number of winners and net approaches and increase in double faults were associated with increased estimated WBGT zone. Conclusions: An association between higher estimated WBGT and medical callouts (heat and non-heat related) was evident, with an increased call rate >32 °C WBGT, despite no heat-related retirements. As estimated WBGT increased, the number of winners and net approaches were reduced, while double faults increased, particularly >30 °C WBGT. Accordingly, the manner in which female players manage and play in the heat during women`s Grand Slam tennis appears to change at ~30 °C WBGT.